Elevated Levels of Peripheral Kynurenine Decrease Bone Strength in Rats with Chronic Kidney Disease - Kalaska, Bartlomiej; Pawlak, Krystyna; Domaniewski, Tomasz; Oksztulska-Kolanek, Ewa; Znorko, Beata; Roszczenko, Alicja; Rogalska, Joanna; Brzoska, Malgorzata M.; Lipowicz, Pawel; Doroszko, Michal; Pryczynicz, Anna; Pawlak, Dariusz (Frontiers in Physiology, 2017)
The diagnosis and treatment of bone disorders in patients with chronic kidney disease (CKD) represent a clinical challenge. CKD leads to mineral and bone complications starting early in the course of renal failure. Recently, we have observed the positive relationship between intensified central kynurenine turnover and bone strength in rats with subtotal 5/6 nephrectomy (5/6 Nx)-induced CKD. The aim of the present study was to determine the association between peripheral kynurenine pathway metabolites and bone strength in rats with 5/6 Nx-induced CKD. The animals were sacrificed one and three months after 5/6 Nx or sham operation. Nephrectomized rats presented higher concentrations of serum creatinine, urea nitrogen, and parathyroid hormone both one and three months after nephrectomy. These animals revealed higher concentrations of kynurenine and 3-hydroxykynurenine in the serum and higher gene expression of aryl hydrocarbon receptor (AhR) as a physiological receptor for kynurenine and AhR-dependent cytochrome in the bone tissue. Furthermore, nephrectomy significantly increased the number of osteoclasts in the bone without affecting their resorptive activity measured in serum. These changes were particularly evident in rats one month after 5/6 Nx. The main bone biomechanical parameters of the tibia were unchanged between nephrectomized and sham-operated rats but were significantly increased in older compared to younger animals. A similar trend was observed for geometrical parameters measured with calipers, bone mineral density based on Archimedes' method and image of bone microarchitecture obtained from micro-computed tomography analyses of tibial cortical bone. In nephrectomized animals, peripheral kynurenine levels correlated negatively with the main parameters of bone biomechanics, bone geometry, and bone mineral density values. In conclusion, our data suggest that CKD-induced elevated levels of peripheral kynurenine cause pathological changes in bone structure via AhR pathway. This finding opens new opportunities for the treatment/prevention of osteoporosis in CKD.